Bioplastic reinforced polyurethane foam and preparation method thereof

By combining modified microalgae powder with polyurethane, bioplastic reinforced polyurethane foam materials with optimized micro-nano structure, surface activity and shear performance were prepared, which solved the problems of complex production process and insufficient performance of bio-based plastics, and significantly improved the impact resistance of the material.

CN119569984AActive Publication Date: 2025-03-07SHENZHEN ANDY NEW MATERIAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411817030.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-07
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The preparation process of bio-based plastics is complex, energy-consuming, and the use of toxic chemicals makes it difficult for the material performance to meet application needs and puts a burden on the environment.

Method used

The microalgae powder is reacted with polyol under mechanical stirring conditions to form the modified microalgae powder, and then mixed with polyether polyol, catalyst, foaming agent and stabilizer, and then molded by casting foaming to prepare bioplastic-reinforced polyurethane foam material.

Benefits of technology

By optimizing the micro-nano structure, surface activity and shear performance, the Young's modulus, compression rebound stress and energy absorption capacity of polyurethane foam materials are significantly improved, and the impact resistance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569984A_ABST
    Figure CN119569984A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses bioplastic reinforced polyurethane foam and a preparation method thereof, relates to the technical field of bioplastics, and aims to solve the technical problem that the performance of bio-based plastics prepared in the prior art is difficult to meet application requirements. The preparation method comprises the following steps: dispersing microalgae powder in deionized water to obtain a microalgae powder dispersion liquid; adding polyol into the microalgae powder dispersion liquid to obtain polyol modified microalgae powder dispersion liquid; drying the polyol-modified microalgae powder dispersion liquid in a drying oven, collecting a solid product, and grinding the solid product into powder by using a grinder to obtain polyol-modified microalgae powder; adding the polyol modified microalgae powder, a catalyst, a foaming agent and a stabilizer into polyether polyol, and continuously stirring to obtain a polyol mixture; the preparation method comprises the following steps: fully mixing a polyol mixture with polyisocyanate under mechanical stirring, and casting a mixed solution into a mold for foaming molding to obtain the bioplastic reinforced polyurethane foam material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of bioplastics, and specifically to a bioplastic reinforced polyurethane foam and a preparation method thereof. Background Art

[0002] In the existing technical field, the preparation process of bio-based plastics faces multiple challenges. Specifically, the raw materials of bio-based plastics need to undergo a series of complex chemical and physical treatment steps, including dissolution, regeneration, cross-linking, centrifugation, water washing, high-temperature drying and hot pressing, before they can be transformed into final products. In this process, the massive consumption of electricity, water resources, materials and human resources is inevitable. At the same time, the use of toxic and hazardous chemicals such as organic solvents, acids, alkalis and salts is also difficult to avoid. This not only fails to effectively reduce the carbon emissions of bio-based plastics during their life cycle, but also poses a significant burden on the environment.

[0003] The core goal of existing technical solutions is to convert bio-based raw materials into solutions, powders, films and other processable forms through physical and chemical means. However, this conversion process is often accompanied by the destruction of the original structure of the material, and there is a lack of effective technology for precise regulation of the microstructure of the material, which makes it difficult to prepare materials with optimal mechanical properties. In addition, there are also significant deficiencies in the technology for regulating the surface functional groups of bioplastics and their intermediates, which directly reduces their processing performance. For example, when used as a reinforcing material, due to the lack of surface functional groups such as free hydroxyl groups, bioplastics are difficult to form a strong bond with matrix materials such as polyurethane. At the same time, the lack of surface hydroxyl groups also leads to a decrease in the dispersibility of bioplastics in water, further weakening their processing performance.

[0004] In terms of strengthening and toughening polyurethane, the existing technology mainly achieves this by introducing rigid, flexible and multiple hydrogen-bonding groups into the polymer structure. The specific process involves adding modified cross-linking agents, chain extenders and other additives during the polymerization of polyurethane. However, the preparation process of modified cross-linking agents and chain extenders is complicated and involves multiple chemical reactions, which further increases the process complexity and environmental cost of polyurethane. In addition, when carbon fiber, glass fiber, etc. are used as reinforcing materials, although surface active groups such as hydroxyl groups can be introduced through surface modification, this process needs to be carried out under harsh reaction conditions, and reinforcing materials such as fibers have limited effect on the shear properties of polyurethane, so it is difficult to significantly improve the impact resistance of composite materials.

[0005] In summary, the preparation of bio-based plastics and their application in polyurethane composites still face many challenges and urgently need further technological innovation and optimization. Summary of the invention

[0006] The main purpose of the present application is to provide a bioplastic reinforced polyurethane foam and a preparation method thereof, aiming to solve the technical problem that the performance of bio-based plastics prepared by the prior art is difficult to meet application requirements.

[0007] To achieve the above objectives, the technical solutions adopted in the embodiments of the present application are as follows:

[0008] In a first aspect, the present application provides a method for preparing a bioplastic reinforced polyurethane foam, comprising the following steps:

[0009] dispersing the microalgae powder in deionized water under mechanical stirring conditions to obtain a microalgae powder dispersion;

[0010] Under mechanical stirring, adding polyol to the microalgae powder dispersion, stirring for 10-15 minutes, heating to 50° C.-80° C., and reacting at the temperature for 2-6 hours to obtain a polyol-modified microalgae powder dispersion;

[0011] placing the polyol-modified microalgae powder dispersion in an oven at 60° C. to 100° C. and drying for 48 to 120 hours, collecting the solid product and grinding it into powder using a pulverizer to obtain polyol-modified microalgae powder;

[0012] Under mechanical stirring, the polyol-modified microalgae powder, catalyst, foaming agent, and stabilizer are added to the polyether polyol, and stirred for 0.5-1 hour to obtain a polyol mixture;

[0013] Under mechanical stirring, the polyol mixture and the polyisocyanate are fully mixed in a ratio of 1:1-4:1, and the mixed solution is cast into a mold for foaming at 60° C.-100° C. to obtain a bioplastic reinforced polyurethane foam material.

[0014] As some optional embodiments of the present application, the microalgae powder includes one or more of Chlorella powder, Nannochloropsis powder, Macroalgae powder, Spirulina powder and seaweed powder, and the particle size of the microalgae powder is 40 mesh-160 mesh.

[0015] As some optional embodiments of the present application, the polyol includes one or more of epoxy resin, polyethylene glycol and castor oil, the molecular weight of the polyol is 800-2000, and the added concentration is 2 mg mL -1 -20mg mL -1 .

[0016] As some optional embodiments of the present application, the catalyst includes one or more of ethylenediamine, N,N-dimethylhexadecylamine, trimethylenediamine, bismuth isooctanoate, bismuth neodecanoate, stannous octoate and dibutyltin dilaurate.

[0017] As some optional embodiments of the present application, the blowing agent includes one or more of water, cyclopentane, n-pentane, isopentane, pentafluoropropane and pentafluorobutane.

[0018] As some optional embodiments of the present application, the stabilizer includes one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, n-octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, polycarbodiimide and monocarbodiimide.

[0019] As some optional embodiments of the present application, the volume fraction of the modified microalgae powder is 0.2%-6.4%.

[0020] As some optional embodiments of the present application, the polyisocyanate includes one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI) and naphthalene-1,5-diisocyanate (NDI).

[0021] In a second aspect, an embodiment of the present application further provides a bioplastic reinforced polyurethane foam, which is prepared by the preparation method of the bioplastic reinforced polyurethane foam as described above.

[0022] As some optional embodiments of the present application, the Young's modulus of the bioplastic reinforced polyurethane foam is 0.2MPa-0.3MPa, the compression rebound stress at a compression rate of 25% is 70kPa-180kPa; the energy absorption capacity is 10.8x10 4 J m -3 .

[0023] Compared with the prior art, the technical solution involved in this application is to enhance the polyurethane foam material by using bioplastics with optimized micro-nano structure, surface activity and shear performance. The optimized micro-nano structure of the bioplastic gives it higher strength characteristics, and the abundant surface free hydroxyl groups enable it to form dynamic and reversible hydrogen bonds with the polyurethane polymer network, while its excellent shear performance effectively improves the strength of the polyurethane matrix when subjected to shear stress such as impact. Compared with polyurethane foam materials that have not been enhanced by bioplastics, the Young's modulus of the bioplastic-enhanced polyurethane foam material in this application is increased by 30%, the compression rebound stress is increased by 13%, and the energy absorption capacity is increased by 11%. That is, this application proposes a simple and environmentally friendly method to achieve the preparation of bioplastics, the optimization of micro-nano structure and the improvement of surface activity. The prepared bioplastic exhibits excellent shear response performance, significantly enhances the impact resistance of polyurethane foam materials, and has broad prospects for application in multiple fields such as sports protection, equipment protection and battery protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the X-ray diffraction pattern of the bioplastic and microalgae powder raw materials prepared in the embodiment of the present invention.

[0025] Figure 2 It is a Fourier infrared spectrum of the bioplastic and microalgae powder raw materials prepared in the embodiments of the present invention.

[0026] Figure 3 The stress-strain curve of the bioplastic reinforced polyurethane foam prepared in the embodiment of the present invention; polyurethane foam with and without microalgae powder added under the same process conditions are used as experimental controls.

[0027] Figure 4 The present invention provides a compression rebound stress-strain curve and an energy absorption bar graph of the bioplastic reinforced polyurethane foam prepared in accordance with an embodiment of the present invention; polyurethane foams with and without microalgae powder added under the same process conditions are used as experimental controls.

[0028] Figure 5 is a scanning electron microscope image of the bioplastic and microalgae powder raw materials prepared in the embodiments of the present invention.

[0029] Figure 6 It is a dynamic light scattering particle size distribution diagram of the bioplastic and microalgae powder raw materials prepared in the embodiments of the present invention.

[0030] Figure 7 This is a scanning electron microscope image of the surface of the bioplastic reinforced polyurethane foam prepared in an embodiment of the present invention; a scanning electron microscope image of the surface of the polyurethane foam added with microalgae powder raw material under the same process conditions is used as an experimental control. DETAILED DESCRIPTION

[0031] It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0032] Micro-nanostructure engineering refers to the process of using physical and chemical means to precisely control the micron- and nano-scale structures of materials to achieve specific physical or chemical properties. Bioplastics refer to plastic products with bio-based materials as the main component, such as bio-based packaging materials, films and sheets, etc., which are usually obtained by processing bio-based materials such as lignin, protein, cellulose, etc. Polyurethane is a polymer material connected by urethane bonds, which is generated by the polymerization reaction of polyisocyanates and polyols. Impact-resistant foam refers to a foamed polymer material that has the function of absorbing impact energy and reducing impact conductivity.

[0033] Traditional plastic materials, such as polyethylene, polypropylene, polyester, etc., are difficult to recycle and degrade naturally, and their excessive use has caused a significant burden on the earth's environment. Using bio-based materials as raw materials and processing them to prepare bio-recyclable and degradable bioplastics is an effective way to solve the pollution of traditional plastics to the natural environment. For example, prior art 1 uses lignin and cellulose as raw materials, and prepares lignin / cellulose bioplastics through alkaline solution dissolution, acid solution regeneration, chemical cross-linking, water washing, high-temperature drying, hot pressing and other process steps; prior art 2 uses cellulose, protein, lignin, tannic acid, tea polyphenols and other raw materials, and prepares degradable bio-based plastics through solvent dissolution, mixing, centrifugation, drying, hot pressing and other steps; prior art 3 uses egg white liquid as raw material, and prepares soft and water-insoluble egg white bioplastics through high-speed centrifugal purification, cooking, drying, heat treatment and other steps; prior art 4 uses waste feathers as raw materials, and prepares high-toughness and high-wet-strength keratin bioplastics through dissolution, centrifugation, salting out, freeze-drying, grinding, dispersion, casting, denaturation, drying and other steps; prior art 5 uses mushroom mycelium fiber membrane as raw material, and prepares mycelium bioplastic film through mycelium culture, glycerol soaking, washing, drying, hot pressing and other steps.

[0034] Polyurethane foam has a wide range of applications in the fields of human and object protection, construction, footwear, artificial leather, etc. By enhancing the mechanical strength and toughness of polyurethane, its application properties such as protection, support, energy absorption, and friction resistance can be significantly improved, and its processing properties such as molding and die cutting can be improved. At present, the methods for enhancing the mechanical properties and toughness of polyurethane mainly include: (1) designing the polymer structure of polyurethane, introducing rigid and flexible groups and hydrogen bonds to improve its mechanical strength and toughness; (2) using fiber materials as structural reinforcement units, dispersing and integrating them into the polyurethane polymer network to form a composite material with higher mechanical properties. For example, prior art 6 effectively improves the strength and toughness of polyurethane foam and reduces the chip drop rate during die-cutting by introducing rigid polycarbonate, flexible polyoxytetramethylene glycol, and hyperbranched polyester structure into the polyurethane polymer structure; prior art 7 introduces the functional group 2-amino-5-(2-hydroxyethyl)-6-methyl-4[1H]-pyrimidone into the polyurethane molecular structure through the chain extender 2,2-dihydroxymethylpropionic acid to form a reversible quadruple hydrogen bond structure, and improves the energy absorption performance and impact resistance of the material through the reversible dissociation of hydrogen bonds; prior art 8 prepares a modified cross-linking agent by condensing 4-(2-hydroxybutyl)phenylethylamine with 4-(2-hydroxybutyl)benzaldehyde, and reacts with polyisocyanate to introduce a hydroxybenzocrown ether ring structure into the polyurethane polymer structure to improve its mechanical strength; at the same time, carbon fiber, glass fiber and other materials are introduced during the molding process to further improve the mechanical strength of the matrix.

[0035] However, in the above-mentioned prior art, the raw materials of bio-based plastics need to undergo complex chemical and physical treatments, such as dissolution, regeneration, cross-linking, centrifugation, water washing, high-temperature drying, hot pressing and other steps, before bio-based plastics can be finally produced. In the process of raw material processing, a large amount of electricity, water, materials, and manpower are consumed, and toxic and harmful chemicals such as organic solvents, acids, alkalis, and salts are used. This can neither effectively reduce the carbon emissions of bio-based plastics in their life cycle, nor does it impose a heavy burden on the environment. In addition, the main purpose of the technical solution is to convert bio-based raw materials into processable solutions, powders, films, etc. through physical and chemical methods. In this process, the original structure of the material is destroyed, and there is a lack of effective methods for precisely controlling the microstructure of the material, making it difficult to obtain materials with optimal mechanical properties.

[0036] It can be seen that the prior art lacks technical solutions for regulating the surface functional groups of bioplastics and their intermediates, which significantly reduces the processing performance of bioplastics and their intermediates. When used as reinforcing materials, bioplastics are difficult to form a strong bond with matrix materials such as polyurethane due to the lack of surface functional groups such as free hydroxyl groups; the lack of surface hydroxyl groups also makes it difficult for bioplastics to disperse evenly in water, thereby reducing their processing performance. In the prior art, reinforcement and toughening are mainly achieved by introducing rigid, flexible and multiple hydrogen bond groups into the polymer structure of polyurethane. The specific process includes adding modified cross-linking agents, chain extenders and other additives during the polymerization of polyurethane. The preparation of modified cross-linking agents and chain extenders requires complex chemical processes, which further increases the process and environmental costs of polyurethane; when carbon fibers, glass fibers, etc. are used as reinforcing materials, surface modification is required under harsh reaction conditions to introduce surface active groups such as hydroxyl groups; these reinforcing materials have little effect on the shear properties of polyurethane and cannot effectively improve the impact resistance of composite materials.

[0037] Based on the above-mentioned deficiencies of the prior art, the present application provides a green preparation method of high-strength bioplastics with optimized micro-nanostructure, surface activity and shear performance, and its application in reinforcing polyurethane impact-resistant materials. The preparation method of the bioplastic reinforced polyurethane foam comprises the following steps:

[0038] dispersing the microalgae powder in deionized water under mechanical stirring conditions to obtain a microalgae powder dispersion;

[0039] Under mechanical stirring, adding polyol to the microalgae powder dispersion, stirring for 10-15 minutes, heating to 50° C.-80° C., and reacting at the temperature for 2-6 hours to obtain a polyol-modified microalgae powder dispersion;

[0040] placing the polyol-modified microalgae powder dispersion in an oven at 60° C. to 100° C. and drying for 48 to 120 hours, collecting the solid product and grinding it into powder using a pulverizer to obtain polyol-modified microalgae powder;

[0041] Under mechanical stirring, the polyol-modified microalgae powder, catalyst, foaming agent, and stabilizer are added to the polyether polyol, and stirred for 0.5-1 hour to obtain a polyol mixture;

[0042] Under mechanical stirring, the polyol mixture and the polyisocyanate are fully mixed in a ratio of 1:1-4:1, and the mixed solution is cast into a mold for foaming at 60° C.-100° C. to obtain a bioplastic reinforced polyurethane foam material.

[0043] As some optional embodiments of the present application, the microalgae powder includes one or more of Chlorella powder, Nannochloropsis powder, Macroalgae powder, Spirulina powder and seaweed powder, and the particle size of the microalgae powder is 40 mesh-160 mesh.

[0044] Preferably, the polyol comprises one or more of epoxy resin, polyethylene glycol and castor oil, the molecular weight of the polyol is 800-2000, and the added concentration is 2 mg mL -1 -20mg mL -1 .

[0045] Preferably, the catalyst comprises one or more of ethylenediamine, N,N-dimethylhexadecylamine, trimethylenediamine, bismuth isooctanoate, bismuth neodecanoate, stannous octoate and dibutyltin dilaurate.

[0046] Preferably, the blowing agent comprises one or more of water, cyclopentane, n-pentane, isopentane, pentafluoropropane and pentafluorobutane.

[0047] Preferably, the stabilizer includes one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, polycarbodiimide and monocarbodiimide.

[0048] Preferably, the volume fraction of the modified microalgae powder is 0.2%-6.4%.

[0049] Preferably, the polyisocyanate includes one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI) and naphthalene-1,5-diisocyanate (NDI).

[0050] The technical solution described in this application is described in detail below in conjunction with specific embodiments:

[0051] Example 1

[0052] Weigh 160-mesh Chlorella powder and add it to deionized water under mechanical stirring to prepare an aqueous dispersion with a mass fraction of 10% of the powder. -1 Weighing a polyethylene glycol with a molecular weight of 2000 and adding it to the dispersion under mechanical stirring; heating the dispersion to 60°C and reacting at this temperature for 3 hours, and then drying it in an oven at 100°C for 48 hours to obtain solidified algae powder aggregates. Grinding the algae powder aggregates into powder using a pulverizer to obtain polyethylene glycol 2000-modified Chlorella powder.

[0053] 100 parts of polyether polyol (VORANOL TM REN 3535) was added to the batching kettle A under mechanical stirring, and 2 parts of pentafluorobutane foaming agent, 1 part of ethylenediamine crosslinking agent, 1 part of triethylenediamine, 0.05 parts of stannous octoate, and 0.7 parts of stabilizer β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate n-octadecyl alcohol ester were added thereto, and 1% volume fraction of modified chlorella powder was added after stirring evenly. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 1:1 and reacted at 95°C for 3 minutes to obtain bioplastic reinforced polyurethane foam.

[0054] Example 2

[0055] Weigh 80-mesh spirulina powder and add it to deionized water under mechanical stirring to prepare an aqueous dispersion with a mass fraction of 10% spirulina powder. -1 Weighing a polyethylene glycol with a molecular weight of 1000 and adding it to the dispersion under mechanical stirring; heating the dispersion to 50°C and reacting at this temperature for 2 hours, and then drying it in an oven at 80°C for 72 hours to obtain solidified algae powder aggregates. Grinding the algae powder aggregates into powder using a pulverizer to obtain polyethylene glycol 1000 modified spirulina powder.

[0056] 100 parts of polyether polyol (VORANOL TM REN 3535) was added to the batching kettle A under mechanical stirring, and 4 parts of pentafluorobutane foaming agent, 7 parts of ethylenediamine crosslinking agent, 2 parts of triethylenediamine, 0.05 parts of stannous octoate, and 0.8 parts of stabilizer β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate were added thereto, and 1.6% volume fraction of modified spirulina powder was added after stirring. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 1.6:1 and reacted at 95°C for 3 minutes to obtain bioplastic reinforced polyurethane foam.

[0057] See also Figure 1, which is the X-ray diffraction pattern of the spirulina powder modified with polyethylene glycol 1000 prepared by the process of Example 2; the X-ray diffraction pattern of the spirulina powder raw material is used as an experimental control. Compared with the spirulina raw material, the α-helical structure of the protein in the spirulina powder modified with polyethylene glycol 1000 is significantly reduced, while the β-sheet folding structure is significantly increased. The increase in β-sheet folding can effectively improve the shear strength and surface free hydrogen bond concentration of the protein material. The test method of the X-ray diffraction pattern is: weigh 5 mg of bioplastic or 5 mg of 80 mesh spirulina powder, fill it in the groove of the glass sample holder, use a glass slide to compact the powder, and scrape off the excess powder above the sample holder. The sample holder is placed on the sample stage of the X-ray diffractometer (Japan Rigaku XRD intelligent X-ray polycrystalline diffractometer) and scanned at a speed of 5° per minute in the range of 5°-90°.

[0058] See also Figure 2 , which is the Fourier transform infrared spectrum of the spirulina powder modified with polyethylene glycol 1000 prepared by the process of Example 2; the Fourier transform infrared spectrum of the raw material of spirulina powder is used as the experimental control. Compared with the raw material of spirulina, the infrared spectrum of the spirulina powder modified with polyethylene glycol 1000 has the peak indicating the hydrogen bond hydroxyl group (3300-3400cm -1 ) intensity decreased significantly, indicating that the number of free hydrogen bonds between its molecules increased significantly. The Fourier transform infrared spectroscopy test method is: weigh 5 mg of bioplastic or 5 mg of 80-mesh spirulina powder, spread it on the sample stage of the attenuated total reflection (ATR) device of the Fourier transform infrared spectrometer (American Thermoelectric Infrared Spectrometer Nicolet iS10) and cover the sampling area, at 16 cm -1 The resolution is 400 cm and the sampling rate is 65 spectra / s. -1 Up to 4000cm -1 The infrared spectra of the samples were collected in a range of wavenumbers.

[0059] See also Figure 3 , which is the stress-strain curve of the bioplastic reinforced polyurethane foam prepared by the process of this embodiment; the polyurethane foam with spirulina powder added and without spirulina powder added under the same process conditions are used as experimental controls. The test method of the stress-strain curve refers to the ASTM D3574 Test E standard, and the slope of the obtained stress-strain curve is the Young's modulus of the sample.

[0060] Comparative Example 1

[0061] Preparation process of polyurethane foam with spirulina powder. 100 parts of polyether polyol (VORANOL TMREN3535) was added to the batching kettle A under mechanical stirring, and 4 parts of pentafluorobutane foaming agent, 7 parts of ethylenediamine crosslinking agent, 2 parts of triethylenediamine, 0.05 parts of stannous octoate, and 0.8 parts of stabilizer β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate were added thereto, and 1.6% volume fraction of 80 mesh spirulina powder was added after stirring. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 1.6:1 and reacted at 95°C for 3 minutes to obtain the polyurethane foam with the spirulina powder raw material added.

[0062] Comparative Example 2

[0063] Preparation process of polyurethane foam without algae powder. 100 parts of polyether polyol (VORANOL TM REN3535) was added to the batching kettle A under mechanical stirring, and 4 parts of pentafluorobutane foaming agent, 7 parts of ethylenediamine crosslinking agent, 2 parts of triethylenediamine, 0.05 parts of stannous octoate, and 0.8 parts of stabilizer β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate were added thereto. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 1.6:1 and reacted at 95°C for 3 minutes to obtain polyurethane foam without algae powder addition.

[0064] See also Figure 4 , which is the compression rebound stress-strain curve and energy absorption bar graph of the bioplastic reinforced polyurethane foam prepared by the process of this embodiment; the polyurethane foam with spirulina powder added and without spirulina powder added under the same process conditions are used as experimental controls. The test method of the compression rebound stress-strain curve refers to the ASTM D1056 standard, with a compression rate of 80%; the test method of the compression rebound stress refers to the ASTM D1056 standard, with a compression rate of 25%. The energy absorption capacity of the sample is the integral area of ​​the compression rebound stress-strain curve below 65% compression rate.

[0065] See Table 1, which compares the mechanical and impact resistance of the bioplastic reinforced polyurethane foam prepared by the process of this embodiment with the performance of the polyurethane foam with or without spirulina powder added prepared under the same process conditions. The test standard for impact conductivity refers to EN1621-1.

[0066] Table 1

[0067]

[0068] Example 3

[0069] Weigh 120-mesh seaweed powder and add it to deionized water under mechanical stirring to prepare an aqueous dispersion with a mass fraction of 15%. -1 The epoxy resin with a molecular weight of 850 was weighed and added to the dispersion under mechanical stirring; the dispersion was heated to 80°C and reacted at this temperature for 2 hours, and then placed in an oven at 80°C for 64 hours to obtain a solidified algae powder aggregate. The algae powder aggregate was ground into powder using a pulverizer to obtain epoxy resin-modified seaweed powder.

[0070] 100 parts of polyether polyol (VORANOL TM REN 3535) was added to the batching kettle A under mechanical stirring, and 5 parts of pentafluoropropane foaming agent, 5 parts of N,N-dimethylhexadecylamine crosslinking agent, 2 parts of triethylenediamine, 0.06 parts of dibutyltin dilaurate, and 1 part of stabilizer tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester were added thereto, and 3% volume fraction of modified seaweed powder was added after stirring evenly. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 2:1 and reacted at 95°C for 3 minutes to obtain bioplastic reinforced polyurethane foam.

[0071] Example 4

[0072] Weigh 40-mesh giant kelp powder and add it to deionized water under mechanical stirring to prepare an aqueous dispersion with a mass fraction of 5% kelp powder. -1 Castor oil with a molecular weight of 930 was weighed and added to the dispersion under mechanical stirring; the dispersion was heated to 60°C and reacted at this temperature for 2 hours, and then placed in an oven at 80°C for 80 hours to obtain solidified algae powder aggregates. The algae powder aggregates were ground into powder using a pulverizer to obtain castor oil-modified giant kelp powder.

[0073] 100 parts of polyether polyol (VORANOL TM REN 3535) was added to the batching kettle A under mechanical stirring, and 3 parts of n-pentane foaming agent, 6 parts of N,N-dimethylhexadecylamine crosslinking agent, 2 parts of triethylenediamine, 0.07 parts of bismuth isooctanoate, and 1 part of stabilizer polycarbodiimide were added thereto, and 1.8% volume fraction of modified giant kelp powder was added after stirring evenly. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 4:1 and reacted at 95°C for 3 minutes to obtain bioplastic reinforced polyurethane foam.

[0074] Example 5

[0075] Weigh 60-mesh Nannochloropsis algae powder and add it to deionized water under mechanical stirring to prepare an aqueous dispersion with a mass fraction of 15%. -1 Weighing a polyethylene glycol with a molecular weight of 1500 and adding it to the dispersion under mechanical stirring; heating the dispersion to 60°C and reacting at this temperature for 2 hours, and then drying it in an oven at 80°C for 64 hours to obtain solidified algae powder aggregates. Grinding the algae powder aggregates into powder using a pulverizer to obtain polyethylene glycol 1500 modified Nannochloropsis algae powder.

[0076] 100 parts of polyether polyol (VORANOL TM REN 3535) was added to the batching kettle A under mechanical stirring, and 3 parts of pentafluoropropane foaming agent, 6 parts of ethylenediamine crosslinking agent, 1.5 parts of triethylenediamine, 0.07 parts of bismuth neodecanoate, and 1 part of stabilizer monocarbodiimide were added thereto, and 2% volume fraction of modified Nannochloropsis powder was added after stirring. MDI was added to the batching kettle B, and the precision metering pump was started. The materials in the batching kettles A and B were cast into the mold through the nozzle at a ratio of 3:1 and reacted at 95°C for 3 minutes to obtain bioplastic reinforced polyurethane foam.

[0077] Example 6

[0078] Weigh 80-mesh spirulina powder and add it to deionized water under mechanical stirring to prepare an aqueous dispersion with a mass fraction of 10% spirulina powder. -1 Weighing a polyethylene glycol with a molecular weight of 1000 and adding it to the dispersion under mechanical stirring; heating the dispersion to 50°C and reacting at this temperature for 2 hours, and then drying it in an oven at 80°C for 72 hours to obtain solidified algae powder aggregates. Grinding the algae powder aggregates into powder using a pulverizer to obtain polyethylene glycol 1000 modified spirulina powder.

[0079] 100 parts of polyether polyol (VORANOL TM REN 3535) is added to the batching kettle A under mechanical stirring, and 5 parts of pentafluorobutane foaming agent, 7 parts of ethylenediamine crosslinking agent, 2 parts of triethylenediamine, 0.05 parts of stannous octoate, and 1 part of polycarbodiimide stabilizer are added thereto, and after stirring evenly, 3% volume fraction of modified spirulina powder is added. MDI is added to the batching kettle B, and the precision metering pump is started, and the materials in the batching kettles A and B are cast into the mold through the nozzle at a ratio of 2:1 and reacted at 95°C for 3 minutes to obtain bioplastic reinforced polyurethane foam.

[0080] See also Figure 5, which is a scanning electron microscope image of the bioplastic prepared by the process of Example 2; the scanning electron microscope image of the spirulina powder raw material is used as an experimental control. It can be seen that compared with the spirulina raw material, the bioplastic has a more angular particle morphology. The testing method of the scanning electron microscope image is: weigh 1 mg of bioplastic or 1 mg of 80-mesh spirulina powder, flatten the spirulina powder and fix it on the aluminum sample stage of the scanning electron microscope using conductive carbon glue, use an ion sputtering device to gold-plate the surface of the spirulina powder, and use a scanning electron microscope (Hitachi Regulus 8100) to observe its microscopic morphology.

[0081] See also Figure 6 , which is the dynamic light scattering particle size distribution diagram of the bioplastic prepared by the process of Example 2; the dynamic light scattering particle size distribution diagram of the spirulina powder raw material is used as the experimental control. It can be seen that compared with the spirulina powder raw material, the bioplastic has a uniform particle size distribution in the aqueous solution. The test method of the dynamic light scattering particle size distribution is: use ultrasonic dispersion to disperse the bioplastic or 80 mesh spirulina powder in deionized water to prepare a concentration of 1 mg mL -1 The dispersion was transferred into a cuvette, and the cuvette was placed in the sample holder of a dynamic light scattering instrument (Malvern ZS90), the instrument was started, and the dynamic light scattering particle size distribution diagram of the sample was obtained.

[0082] See also Figure 7 , which is a scanning electron microscope image of the bioplastic reinforced polyurethane foam prepared by the process of Example 2; the scanning electron microscope image of the polyurethane foam with spirulina powder added as the experimental control. It can be seen that compared with the polyurethane foam with spirulina powder added, the bioplastic reinforced polyurethane foam has a smoother surface structure.

[0083] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing bioplastic reinforced polyurethane foam, characterized in that: The following steps are involved: dispersing the microalgae powder in deionized water under mechanical stirring conditions to obtain a microalgae powder dispersion; Under mechanical stirring, adding polyol to the microalgae powder dispersion, stirring for 10-15 minutes, heating to 50° C.-80° C., and reacting at the temperature for 2-6 hours to obtain a polyol-modified microalgae powder dispersion; placing the polyol-modified microalgae powder dispersion in an oven at 60° C. to 100° C. and drying for 48 to 120 hours, collecting the solid product and grinding it into powder using a pulverizer to obtain polyol-modified microalgae powder; Under mechanical stirring, the polyol-modified microalgae powder, catalyst, foaming agent, and stabilizer are added to the polyether polyol, and stirred for 0.5-1 hour to obtain a polyol mixture; Under mechanical stirring, the polyol mixture and the polyisocyanate are fully mixed in a ratio of 1:1-4:1, and the mixed solution is cast into a mold for foaming at 60° C.-100° C. to obtain a bioplastic reinforced polyurethane foam material.

2. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The microalgae powder comprises one or more of chlorella powder, Nannochloropsis powder, giant kelp powder, spirulina powder and seaweed powder, and the particle size of the microalgae powder is 40-160 meshes.

3. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The polyol comprises one or more of epoxy resin, polyethylene glycol and castor oil, the molecular weight of the polyol is 800-2000, and the added concentration is 2 mg mL -1 -20mg mL -1 .

4. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The catalyst includes one or more of ethylenediamine, N,N-dimethylhexadecylamine, trimethylenediamine, bismuth isooctanoate, bismuth neodecanoate, stannous octoate and dibutyltin dilaurate.

5. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The blowing agent includes one or more of water, cyclopentane, n-pentane, isopentane, pentafluoropropane and pentafluorobutane.

6. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The stabilizer includes one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, polycarbodiimide and monocarbodiimide.

7. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The volume fraction of the modified microalgae powder is 0.2%-6.4%.

8. The method for preparing bioplastic reinforced polyurethane foam according to claim 1, characterized in that: The polyisocyanate includes one or more of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI) and naphthalene-1,5-diisocyanate (NDI).

9. A bioplastic reinforced polyurethane foam, characterized in that: The bioplastic reinforced polyurethane foam is prepared by the preparation method of any one of claims 1 to 8.

10. The bioplastic reinforced polyurethane foam according to claim 9, characterized in that: The Young's modulus of the bioplastic reinforced polyurethane foam is 0.2MPa-0.3MPa, the compression rebound stress at a compression rate of 25% is 70kPa-180kPa, and the energy absorption capacity is 10.8x 10 4 J m -3 .

Citation Information

Patent Citations

  • Polyurethane foam insulation material and preparation method thereof

    CN109535688A

  • Preparation method of diatom slow-rebound material

    CN112079990A

  • Polyurethane of increased of biomass-content as well as improvement of material property by filling or reacting modified-microcrystalline cellulose , and preparation methods thereof

    KR1020180128251A

  • Algae-derived flexible foam, and method of manufacturing the same

    US20170066893A1

  • Algae-blended thermoplastic compositions

    US20200283600A1